Filsafat Organisme Alfred North Whitehead dan Implikasinya pada Pendidikan - Entoh Tohani (LPPM Press, 2012)
There are many philosophers in the world gave his/her influences to development ofeducational world, whith difference of their thinking chacteristic. One of who emerged in early 20thcentury is Alfred North Whitehead. His thought viewed that the human are a creature whichindependently regulate her/his self in process of interaction with others in which is no domination. Histhought has directed educational practices both on teaching and learning and on educationalmanagement in order to be run well and goal oriented. The main focus is leaner viewed as individu whomust be developed humanizely.